2014
DOI: 10.3390/ijms15033624
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic Activities of Aporphine from Nelumbo nucifera Gaertn. cv. Rosa-plena against Hymenolepis nana

Abstract: Nelumbo nucifera Gaertn. cv. Rosa-plena (Nelumbonaceae), commonly known as lotus, is a perennial aquatic plant grown and consumed throughout Asia. All parts of N. nucifera have been used for various medicinal purposes in oriental medicine. From the leaves of Nelumbo nucifera Gaertn. cv. Rosa-plena (an aquatic plant), liriodenine (1), lysicamine (2), (−)-anonaine (3), (-)-asimilobine (4), (-)-caaverine (5), (-)-N-methylasimilobine (6), (-)-nuciferine (7), (-)-nornuciferine (8), (-)-roemerine (9), 7-hydroxydehyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The leaves, flowers, seeds and rhizomes of these plants have been broadly used in traditional medicine for treating a spectrum of ailments (Mukherjee et al., 2009). Aporphine compounds isolated from Nelumbo nucifera leaves have been previously shown to have anticestodal profiles, with the mechanistic basis for these effects being ascribed to a free radical scavenging effect (Lin et al., 2014). A more recent study investigating the psychotropic properties of nuciferine demonstrated an affinity for several mammalian serotonergic GPCRs, encompassing action as an inverse agonist at the human 5-HT 7 receptor (Hs.5HT 7 R (Farrell et al., 2016)).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The leaves, flowers, seeds and rhizomes of these plants have been broadly used in traditional medicine for treating a spectrum of ailments (Mukherjee et al., 2009). Aporphine compounds isolated from Nelumbo nucifera leaves have been previously shown to have anticestodal profiles, with the mechanistic basis for these effects being ascribed to a free radical scavenging effect (Lin et al., 2014). A more recent study investigating the psychotropic properties of nuciferine demonstrated an affinity for several mammalian serotonergic GPCRs, encompassing action as an inverse agonist at the human 5-HT 7 receptor (Hs.5HT 7 R (Farrell et al., 2016)).…”
Section: Discussionmentioning
confidence: 99%
“…A clinically well-known example is apomorphine, a synthetic morphine derivative used clinically as an anti-Parkinsonian agent due to efficacy at dopaminergic GPCRs. Several aporphine compounds have previously been demonstrated to impair neuromuscular function in a variety of helminth parasites (Ayers et al., 2007, Chan et al., 2014, Lin et al., 2014), although the molecular target of these drugs in parasites is uncharacterized. The affinity of aporphinoids for mammalian 5-HT GPCRs (Munusamy et al., 2013, Ponnala et al., 2014, Ponnala et al., 2015, Farrell et al., 2016) was especially intriguing to us in this context.…”
Section: Introductionmentioning
confidence: 99%
“…The anthelmintic efficacy of plant extract may be due to the presence of secondary metabolites particularly the alkaloids (Lin et al 2010). Extracts of several medicinal plants have been tested and proved to be effective against many helminth parasites (Abdel-Ghaffar et al 2011;Li et al 2012;Lin et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Anti-bacterial and anti-fungal effect. Lin et al isolated ten aporphine derivatives from N. nucifera and discovered their anthelmintic activities against A. simplex and H. nana (Lin et al, 2014). Moreover, Brindha et al tested the efficacy of hydroethanolic extract of N. Nucifera flower against five important bacterial strains and two fungal strains.…”
mentioning
confidence: 99%
“…(Continued)Chang et al, 2016;Duan et al, 2014;Liu et al, 2014b;Lin et al, 2014) 42 7-hydroxydehy dronuciferine (7HDNF)Leaves(Wafo et al, 1999;Wu et al, 2015a) 43 Pronuciferine Seeds, Fruits, Leaves(Wang et al, 1991;Kunitomo et al, 1973;Kashiwada et al, 2005;Li et al, 2014;Ma et al…”
mentioning
confidence: 99%